Direct Amination of Benzylic Pinacol Boronates by an Aminoazanium - Xu, Jianeng; Qin, Yucheng; Liu, Chao (Synlett, 2023)
A practical stereospecific direct amination of benzylic pinacol boronates was achieved by using 4-amino-4-methylmorpholinium iodide as a new amination reagent and cesium carbonate as the base. After amination, an in situ reductive N-alkylation with an aldehyde proceeded well to produce secondary amines.
Keywords: benzylic pinacol boronates; amination; asymmetric synthesis; secondary amines; aminomethylmorpholinium iodide